2022
DOI: 10.3389/fpsyg.2022.780675
|View full text |Cite
|
Sign up to set email alerts
|

“I’ll Worry About It Tomorrow” – Fostering Emotion Regulation Skills to Overcome Procrastination

Abstract: Procrastination remains an omnipresent phenomenon impeding especially students’ academic performance and well-being. Preliminary findings suggest that procrastination emerges due to dysfunctional emotion regulation efforts to regulate aversive emotions. This study’s objective was to clarify whether the enhancement of general adaptive emotion regulation skills reduces subsequent procrastination. For the purpose of this study, data from a two-armed randomized controlled trial (RCT) with (N = 148) university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…Ambas podrían representar las dos vías neurales subyacentes al impacto marcadamente inverso de la escrupulosidad sobre la procrastinación, y las dos se asocian positivamente con el grado de conciencia. (34) La mejora de las habilidades generales para regular las emociones parece eficaz en reducir el posterior comportamiento procrastinador (35) . Asimismo, hay intervenciones favorables no sanitarias apoyadas en métodos que implementan la llamada "conciencia plena" o mindfulness (36,37) , y algunas otras prácticas relativamente próximas como el yoga.…”
Section: Resultados Y Discusiónunclassified
“…Ambas podrían representar las dos vías neurales subyacentes al impacto marcadamente inverso de la escrupulosidad sobre la procrastinación, y las dos se asocian positivamente con el grado de conciencia. (34) La mejora de las habilidades generales para regular las emociones parece eficaz en reducir el posterior comportamiento procrastinador (35) . Asimismo, hay intervenciones favorables no sanitarias apoyadas en métodos que implementan la llamada "conciencia plena" o mindfulness (36,37) , y algunas otras prácticas relativamente próximas como el yoga.…”
Section: Resultados Y Discusiónunclassified
“…Resilience and EI could mutually promote each other, and the higher individual's EI is, the better one can control his or her own emotion (Zhang et al., 2019 ). In summary, incorporating EI development into course curricula may increase students' resilience, thereby indirectly influencing AP (Eckert et al., 2016 ; Schuenemann et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those who always deliberately procrastinate their study missions were more likely to have psychological problems and higher suicidal tendency (Flett et al., 2016 ; Steel, 2007 ). Therefore, lowering AP level is critical to improving educational outcomes such as academic achievement, emotional regulation and psychological resilience (Miraj et al., 2021 ; Mohammadi et al., 2020 ; Schuenemann et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important mechanism involved in procrastination seems to be related to dysfunctional emotional regulation, especially of negative emotions (e.g., Tice and Baumeister, 1997 ; Tice and Bratslavsky, 2000 ; Sirois and Pychyl, 2013 , 2016 ; Pollack and Herres, 2020 ), interventions that focus on emotion regulation skills are indicated. Indeed, using the Adaptive Coping with Emotions Model (ACE Model; Berking and Whitley, 2014 ), Schuenemann et al (2022) demonstrated that an intervention to train emotion regulation skills can reduce procrastination. Inspecting the ACE Model, effective emotion regulation addresses several aspects related to the antecedent part of the ABC model, such as emotion perception (i.e., to be aware and correctly identify and label emotions), identification of causes and maintaining conditions for emotions, the ability to tolerate negative emotions when necessary (i.e., emotional resilience), being able to a pproach and confront situations that are likely to trigger negative emotions, and being able to provide self-support in distressing situations .…”
Section: A Functional Analysis Of Academic Procrastination: Summing Upmentioning
confidence: 99%